2021
DOI: 10.32872/cpe.3645
|View full text |Cite
|
Sign up to set email alerts
|

Medication-enhanced psychotherapy for posttraumatic stress disorder: Recent findings on oxytocin’s involvement in the neurobiology and treatment of posttraumatic stress disorder

Abstract: Background Traumatic experiences may result in Posttraumatic Stress Disorder (PTSD), which is characterized as an exaggerated fear response that cannot be extinguished over time or in safe environments. What are beneficial psychotherapeutic treatment options for PTSD patients? Can oxytocin (OXT), which is involved in the stress response, and safety learning, ameliorate PTSD symptomatology and enhance psychotherapeutic effects? Here, we will review recent studies regarding OXT’s potential to enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“…Although oxytocin has relieving effect on PTSD symptoms, it has been reported that it is not clinically significant. However, it has been claimed that it can improve arousal and memory impairment when applied together with psychotherapy used in PTSD 33 , 34 .…”
Section: Oxytocin For Treating Post-traumatic Stress Disordermentioning
confidence: 99%
“…Although oxytocin has relieving effect on PTSD symptoms, it has been reported that it is not clinically significant. However, it has been claimed that it can improve arousal and memory impairment when applied together with psychotherapy used in PTSD 33 , 34 .…”
Section: Oxytocin For Treating Post-traumatic Stress Disordermentioning
confidence: 99%